Pengaruh Ketimpangan Gender Terhadap Pembangunan Ekonomi Inklusif Di Indonesia - Wifa Afrida Jumiati; Yeniwati (Universitas Negeri Padang, 2025)
This research examines how gender disparities in health, education, and consumption allocation influence inclusive economic development in Indonesia. Using provincial panel data spanning 2013 to 2023 and employing a fixed effects regression approach, the study finds that all measures of gender inequality have a positive and statistically significant impact on the Inclusive Economic Development Index (IPEI).